2023
DOI: 10.1111/1346-8138.16843
|View full text |Cite
|
Sign up to set email alerts
|

Single‐center survey of incidental imaging findings on computed tomography in patients with psoriasis on biologic therapy

Abstract: Psoriasis is one of the most common chronic inflammatory skin diseases and predominantly affects the skin and joints. 1,2 Various comorbidities and risk factors interact with each other and affect the pathogenesis of psoriasis. 3 Metabolic syndrome is strongly associated with the onset and exacerbation of psoriasis, and patients with psoriasis are at increased risk of cardiovascular disease, which is ascribed not only to metabolic syndrome but also to chronic systemic inflammation. 4 Additionally, patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…In patients with moderate-to-severe psoriasis, CT frequently reveals fatty liver disease, urolithiasis, and gallstones [2]. In this past study, multivariate logistic regression was performed to estimate the effect of psoriasis while adjusting for confounding factors such as age, body mass index, sex, type 2 diabetes mellitus, hypertension, and dyslipidemia [2]. The results showed that psoriasis was a risk factor for fatty liver disease, urolithiasis, and gallstones.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…In patients with moderate-to-severe psoriasis, CT frequently reveals fatty liver disease, urolithiasis, and gallstones [2]. In this past study, multivariate logistic regression was performed to estimate the effect of psoriasis while adjusting for confounding factors such as age, body mass index, sex, type 2 diabetes mellitus, hypertension, and dyslipidemia [2]. The results showed that psoriasis was a risk factor for fatty liver disease, urolithiasis, and gallstones.…”
mentioning
confidence: 97%
“…
Dear Editors, Psoriasis is one of the most common immune-mediated, chronic inflammatory diseases that predominantly affect the skin and joints [1]. Recently, we demonstrated that fatty liver disease, urolithiasis, and gallstones are frequently observed upon computed tomography (CT) of patients with psoriasis, and that psoriasis is a risk factor for the development of such comorbidities [2]. The aim of this study was to determine whether specifically the presence of psoriatic arthritis (PsA) is a risk factor for fatty liver disease, urolithiasis, and gallstones.This study was approved by the Ethical Committee of Jichi Medical University.
…”
mentioning
confidence: 99%
See 3 more Smart Citations